Bacterial infection associated with respiratory cystic fibrosis in Hilla City - Obaid, Ali J.; Al-Hindawi, Rabeea A.; Naser, Maryam S. (Scientific Journal of Medical Research, 2024)
Background: The majority of autosomal genetic diseases in North America are caused by CF, which affects 1 in 2000 Caucasians. This illness can, in many circumstances, be asymptomatic and affects people of all ages and genders. Acute and frequent bacterial infections, inflammation, obstruction of the airways, and chronic bacterial infections are all made more likely due to weak innate defenses and inadequate mucociliary clearance in the airways. Aim of study: The present study aims to detect and identification of bacterial species associated with respiratory fibrosis and make a sensitivity test for each species. Methodology: The present study done in a period between January to July 2023, including 80 cystic fibrosis patients who arrived to Hilla’s hospitals, 50 of each in outpatient clinic and 30 sleeping in hospital (12 of them in RCU and 18 in respiratory lobbies), age of patients among present study (20-80 years), and include both gender were (28 females and 52 males). Sputum was collected from all patients by using sterile labeled containers after that transported to the laboratory directly after collection and stored at 4 C until culture. All sputum samples were cultured on McConkey agar and Blood agar for 24 hours, and the incubation temperature was maintained at 37 C. Following this, bacterial colonies were isolated using a variety of selective and differential media, and after 24 hours of incubation, biochemical tests were performed to identify the species of bacteria. Isolated bacterial colonies were then taken, and they were cultured on Muller-Hinton agar using a variety of antibiotic discs, and conventional approach of measuring inhibition zones was used to assess the antibiotic sensitivity and resistance of microorganisms. Results: The result of the current study appeared to show an effect of age in the infection with microbial CF. The present results showed 9 patients in the age group (20–30 years) from 80 total (11.25%), while in the (31–40 years) age group 11 patients (13.75%), in the (41–50 years) age group the results showed there are 16 patients in percentage 16.25%, and in the (51–60 years) age group there are 17 patients (21.25%). In the (61–70) age group, there are 20 patients in the 25% percentage, while finally, in the (71–80) age group, there were 10 patients (12.5%). The present study confirmed an increase in infection with age. In the field of gender, the current study confirmed infection in males more than in females, with 52 males (65%) percentage and 28 females (35%). Distribution of bacterial species among samples The following bacteria species were discovered in the current study: 17 samples of Mycobacterium sp. In 21.25% of Staphylococcus aureus (17.5%) samples, 13 samples of MRSA (16.25%), 8 samples of Pseudomonas aeruginosa in (10%), and 7 samples of Burkholderia ssp. In (8.75%) percentage, 6 samples of Achromobacter xylosoxidans in (7.5%), 3 samples of Inquilinus limosus in (3.75%) percentage, 1 sample of Ralstonia sp. In(1.25%), 5 samples of Streptococcus pneumonia (6.25%), 1 sample of Stenotrophomonos maltophilia (1.25%), 2 samples of Haemophilus influenza (2.5%). Conclusion: The probability of transmission is influenced by many variables, including the specific bacteria involved, the patient’s immune system, and the cleanliness of the hospital’s instruments. All cystic fibrosis patients who have been colonized or infected with the primary pathogens discussed here should be quarantined in a single room. points of nosocomial transmission to other patients during therapy. Although the epidemiology of bacterial infections in people with CF is complicated, the average lifespan of people with CF continues to rise.